Inositol and herbal substances as elements of complementary therapy in patients with PCOS - Arkadiusz Aab; Julia Zarańska; Kamila Kędra; Izabela Michalik; Maciej Bielak; Bartosz Zarański (Kazimierz Wielki University, 2023)
Introduction: Polycystic ovary syndrome is a common hormonal disorder in women and the leading cause of female infertility. Traditional therapeutic methods often do not yield the expected results, hence the need to explore new treatment strategies. Promising results have been observed in studies on inositol. Objective: The aim of this study is to summarize the current knowledge regarding the effectiveness and safety of inositol and herbal preparations in the treatment of PCOS based on available scientific literature. Materials and Methods: A literature review was conducted using PubMed and Google Scholar databases, using search terms: inositol, PCOS treatment, herbal medicine in PCOS. Current knowledge: Inositol is an oral supplement used in the therapy of PCOS. It is characterised by high safety and minimal risk of side effects. Herbal extracts alleviate symptoms in patients with PCOS. Conclusions: Analysis of scientific research has provided evidence of the effectiveness of inositol, particularly myo-inositol, in complementary therapy for PCOS. Herbal medicine also appears to be an effective supportive treatment. However, these substances should not be considered as primary therapy but rather as an adjunct. Only both - primary medications and complementary treatment methods, can yield a therapeutic effect.